NESTING AND SURVIVAL OF RIO GRANDE TURKEYS IN NORTHCENTRAL TEXAS - Scott D. Hohensee; Mark C. Wallace (Wildlife Society Bulletin)
Abstract: We studied survival and habitat use of female Rio Grande turkeys (Meleagris gallopavo intermedia) during the nesting period in the Rolling Plains and Cross Timbers ecotone of northcentral Texas. Mortalities occurred during movement from winter roosts and during nesting. Survival and nest success were related to timing and amounts of precipitation. Turkeys nested in herbaceous or woody vegetation that was taller, shaded the nest bowl more, and provided greater visual obstruction than adjacent sites. Winter wheat fields attracted nesting turkeys and nest success was similar to that on rangelands.